Socio-hygienic factors management of human resources of the industrial enterprise - A. A. Gusova (Путеводитель предпринимателя)
In the article the problems of improvement of sanitary-hygienic and psycho-physiological conditions of employees of industrial enterprises as an integral part of the management system of human resources.